Fine-grained Patterns of the Digital Divide: Differences of Broadband Access within Finland - Heikki Eskelinen; Lauri Frank; Timo Hirvonen (European Regional Science Association (ERSA), 2003)
Access to the Internet plays a central role in the development of an information society. However, because of the required telecommunications infrastructure is very expensive to build, and telecommunications services are also relatively expensive, there is no sufficient demand for a market-based provision of relevant telecommunication infrastructures in many areas. As a result, some citizens and organisations are left without an (up-to-date) access to the Internet. This gap between social groups with and without access to the Internet, which is also often linked with a lack of motivation to use it, is referred to as Digital Divide. Several governments have implemented programmes aimed at diminishing this Divide, by means of providing access to the Internet in regions where the market does not provide it, and by enhancing the citizens' ?information society? skills and motivation. There are a variety of technologies available for connecting to the Internet. The traditional narrowband means include modem and ISDN. For faster connections in terms of data transfer rate, various broadband technologies have been introduced. Actually, these broadband connections, which usually offer a fixed pricing scheme, are often seen as the embodiment of an information society. Lately, also mobile connections have become a feasible in creating an access to the Internet, as their speed has increased to the level of the traditional modem connection, and their data transfer prices have been reduced. The aim of this paper is to explore spatial patterns and differences in internet access in Finland. Availability of all possible technologies (traditional, broadband and mobile) are investigated in detail. The findings are compared with demographic characteristics of the relevant regions. Not surprisingly, the tentative results support the view that regions with higher population densities have a better access to the Internet. With regard to the debate on the Digital Divide, it is especially interesting to observe that variations in access to the Internet do not follow administrative borders, but are much more fine-grained. Clearly, this has implications for effective and righteous information society policies, and for an evaluation of the effectiveness of such policies. The paper in an outgrowth of the project ?Telecommunications Services and Networks and Territorial Cohesion? funded from the European Spatial Planning Observation Network (ESPON) programme (see www.espon.lu). Key words: internet access, digital divide, telecommunications infrastructure, spatial differences, ESPON
Keywords: 330